RLS based TDOA-DV Localization in Sensor Network - Chinna Kullayappa, Kanekal; Varadarajan, S; Soundararajan, K (International Journal of Engineering and Technology, 2018)
Real-time randomly deployed sensor nodes require precise location estimates. The master nodes equipped with GPS and are aware of their locations, help the sensor nodes in estimating their locations by transmitting dual velocity beacon time stamped signals along with their location information. The sensor nodes in the collection of data, compute location using Time Difference of Arrival with Dual Velocity (TDOA-DV) technique. In this paper, Recursive Least Square (RLS) based TDOA-DV localization technique was discussed and its influence on (i) the rate at which the sample data from master nodes to be collected & (ii) the number of samples used for the regression analysis. The results show that RLS based TDOA-DV technique can achieve high precision in location estimation and also improve the number of samples required. The results are compared to TDOA technique.Â Â